Three-dimensional heterotypic colorectal cancer spheroid models for evaluation of drug response - Yau, Jia Ning Nicolette; Adriani, Giulia (Frontiers in Oncology, 2023)
Colorectal cancer (CRC) is a leading cause of death worldwide. Improved preclinical tumor models are needed to make treatment screening clinically relevant and address disease mortality. Advancements in 3D cell culture have enabled greater recapitulation of tumor architecture and heterogeneity in the tumor microenvironment (TME), enhancing their pathophysiological relevance and enabling more accurate predictions of tumor progression and drug response in patients. An increasing number of 3D CRC spheroid models include cell populations such as cancer-associated fibroblasts (CAFs), endothelial cells (ECs), immune cells, and gut bacteria, enabling greater correlation with the in vivo regulation of signaling pathways. Furthermore, cell heterogeneity enables the identification of new therapeutic targets and test alternative treatments, such as cancer immunotherapy. In this mini review, we present the advances in mimicking tumor heterogeneity in 3D CRC spheroid models by incorporating CAFs, ECs, immune cells, and gut bacteria and their influence on chemoresistance and tumor progression of CRC spheroids. We also highlight important parameters to evaluate during drug screening in these multi-cellular spheroids.